Effect of land use change on ecosystem function of dung beetles: experimental evidence from Wallacea Region in Sulawesi, Indonesia - SHAHABUDDIN SHAHABUDDIN (Society for Indonesian Biodiversity, 2011)
Shahabuddin (2011) Effect of land use change on ecosystem function of dung beetles: experimental evidence from Wallacea Region in Sulawesi, Indonesia. Biodiversitas 12: 177-181. The deforestation of tropical forests and their subsequent conversion to humandominated land-use systems is one of the most significant causes of biodiversity loss. However clear understanding of the links between ecological functions and biodiversity is needed to evaluate and predict the true environmental consequences of human activities. Thisstudy provided experimental evidence comparing ecosystem function of dung beetles across a land use gradient ranging from natural tropical forest and agroforestry systems to open cultivated areas in Central Sulawesi. Therefore, standardized dung pats were exposed at each land-use type to assess dung removal and parasite suppression activity by dung beetles. The results showed that ecosystem function of dung beetles especially dung burial activity was remarkably disrupted by land use changes from natural forest to open agriculturalarea. Dung beetles presence enhanced about 53% of the total dung removed and reduced about 83% and 63% of fly population and species number respectively, indicating a pronounce contribution of dung beetles in our ecosystem.